LACK OF MOTIVATION: A NEW MODIFIABLE RISK FACTOR FOR PERITONITIS IN PATIENTS UNDERGOING PERITONEAL DIALYSIS?. Issue 1 (19th November 2014) - Paudel, Klara; Namagondlu, Girish; Samad, Nasreen; McKitty, Khadija; Fan, Stanley L.
SUMMARY Aim Can we identify modifiable risk factors for peritonitis in patients undergoing peritoneal dialysis (PD)? We aimed to determine whether housing standard, PD exchange technique or patient motivation might be modifiable risks for peritonitis. We also explored the relationship between lack of motivation and depression. Methods Nurse home visits assessed PD exchange technique, environment and patient motivation. Motivation scores were correlated separately with an Apathy Evaluation Score and a depression score using PHQ‐9 questionnaires. Results Home hygiene, exchange technique and motivation were above average in 53%, 56% and 60%, respectively in 104 patients undergoing PD. After 15 months, 25.9% patients developed peritonitis but nurses' ratings of homes and exchange techniques were not predictive. Low patient motivation was predictive. Patients rated to have above or below median motivation had significantly different Apathy Scores (p = 0.0002). Unmotivated depressed patients were significantly more likely to develop peritonitis compared to motivated depressed patients. Conclusion Lack of motivation predicted peritonitis particularly if associated with depression. Further studies are required focusing on specific motivation scoring schemes and the psychosocial support that might lead to better outcomes.